Lorentz invariance violation induced threshold anomaly versus very-high energy cosmic photon emission from GRB 221009A - Li, Hao; Ma, Bo-Qiang (Astroparticle physics, 2023)
It has been reported that the Large High Altitude Air Shower Observatory (LHAASO) observed very high energy photons from GRB 221009A, with the highest energy reaching 18 TeV. We find that observation of such high energy photons is quite nontrivial since extragalactic background light could absorb these photons severely and the flux is too weak to be observed. Therefore we discuss a potential mechanism for us to observe these photons, and suggest that Lorentz invariance violation induced threshold anomaly of the process γγ→e−e+ provides a candidate to explain this phenomenon.